Determination of conditions for motivating the Development of key competencies of higher Education students - Dmytrenko, Kateryna; Kapustina, Olena; Kharkivska, Aryna; Korsikova, Kateryna; Molchaniuk, Olha; Onypchenko, Oksana (My University, 2021)
The article defines the concept of "competence", which allows discussing the academic culture model as a set of educational competencies. As key competencies are not only a system of knowledge, skills and attitudes, but the ability to apply them in a specific situation to solve everyday problems effectively. In the process of professional development in higher education, how competencies are designed from the objectives of the courses, expanding the personal and social experience in the area of knowledge and beyond. It is concluded that the conditions for the development of competencies should not be well used, since they are provocations from the field of knowledge.
Determination of conditions for motivating the Development of key competencies of higher Education students / K. Dmytrenko, O. Kapustina, A. Kharkivska, K. Korsikova, O. Molchaniuk, O. Onypchenko // Laplage em Revista (International), sept. - dec. 2021. – Vol. 7. – N. 3A. – P. 361–369.
Keywords: мотивація, потреби, пізнавальна активність, професійний розвиток, вища освіта; motivation, needs, cognitive activity, professional development, higher education.